Management Staff by International Comparison: Most of the Women on Supervisory Boards in Germany are Works Council Representatives - Elke Holst (Weekly Report, 2005)
In June 2004 only about one tenth of all the seats on the boards of the 200 biggest companies worldwide were held by women. In 22 of these companies women held at least 25% of the seats on the board. Three of the companies were German. Here the percentage is made up entirely of women who represent the workforce. In 72 of the 100 biggest companies in Germany at least one member of the supervisory board is a woman (7.5% of the total number of seats); more than 80% of these women acquired their seat through the works council. This sobering figure on corporate management is largely a result of the low number of women in top management jobs compared with men. According to information from companies women currently account for about one tenth of the management jobs in Germany. And although progress has been made in some areas in the past decade, an equal distribution of top jobs between men and women is still a distant prospect. In view of the considerable social and demographic changes now underway, it is essential to make better use of the potential of highly qualified women to ensure that the German economy remains competitive. Hence it is proposed to set up a high-ranking 'Glass Ceiling Commission', similar to the one in the United States. It should work out the economic and social consequences of this problem with the cooperation of the private sector, and develop recommendations on the measures and binding framework conditions that may be necessary. That could help to overcome the barriers to the promotion of women into management and decision-making positions.
Keywords: 330